Enzyme-linked fluorescent immunoassay for monitoring the herbicide active ingredient glyphosate in water - Takács Eszter; Gémes Borbála; Szendrei Fanni; Keszei Csaba; Barócsi Attila; Lenk Sándor; Domján László; Mörtl Mária; Klátyik Szandra; Székács András; 28th International Symposium on Analytical and Environmental Problems Szeged 2022. november 14-15. (2022)
Within a modular water quality assessment fluorimeter instrument family, a newly developed enzyme-linked fluorescent immunoassay has been utilized for the quantitative analytical measurement of the herbicide active ingredient glyphosate in surface water. The developed 96- well microplate-based competitive immunoassay with fluorescence detection provides a 2.5- fold lower limit of detection (LOD = 0.09 ng/mL) in the investigated concentration range of glyphosate (0–100 ng/mL) compared to the detection of visual absorbance signals. Additionally, fluorescence detection resulted in a wider dynamic range for glyphosate measurement. Matrix effect was not observed for the undiluted surface water samples, and cross-reaction was not detected between glyphosate and its main metabolite (Naminomethylphosphonic acid) and structurally similar compounds. The method allows rapid monitoring of glyphosate as a ubiquitous water contaminant of agricultural origin that can affect, due to its global use, both aquatic and terrestrial ecosystems.
Keywords: Természettudományok; Kémiai tudományok